1999
DOI: 10.1002/(sici)1521-3935(19990101)200:1<231::aid-macp231>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Interpenetrating hydrogel networks based on polyacrylamide and poly(itaconic acid): synthesis and characterization

Abstract: SUMMARY: The synthesis of sequential and simultaneous semi-interpenetrating hydrogel networks (IPNs) based on polyacrylamide (PAAm) and poly(itaconic acid) (PICA) is described. Polyacrylamide was used as a host polymer. Physical properties of IPN hydrogels were determined by IR, swelling, extraction and density measurements. No indication for the formation of hydrogen-bonded complexation was observed by IR spectroscopy. The extraction results showed that the grafting level between the two components of PAAm/PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The broad and weak bands at 2500-3700 cm À 1 and 1648 cm À 1 were associated with H 2 O [18,24,31]. PAAm was characterized with the main absorptions at 3200-3400 cm À 1 of N-H stretches, at 1640 cm À 1 of amide (C¼O stretching and N-H bending), at 1425 cm À 1 of C-N stretching and at 700 cm À 1 of N-H out-of plane bending [37,38]. PAAm-HAP profile containing all characteristic peaks was the evidence for fine incorporation of inorganic and organic phases within the composite as discussed by Bajpai and Bundela [30].…”
Section: Structural Evaluationmentioning
confidence: 99%
“…The broad and weak bands at 2500-3700 cm À 1 and 1648 cm À 1 were associated with H 2 O [18,24,31]. PAAm was characterized with the main absorptions at 3200-3400 cm À 1 of N-H stretches, at 1640 cm À 1 of amide (C¼O stretching and N-H bending), at 1425 cm À 1 of C-N stretching and at 700 cm À 1 of N-H out-of plane bending [37,38]. PAAm-HAP profile containing all characteristic peaks was the evidence for fine incorporation of inorganic and organic phases within the composite as discussed by Bajpai and Bundela [30].…”
Section: Structural Evaluationmentioning
confidence: 99%
“…Some research has dealt with hydrogels based on polyacrylamide and itaconic acid or its esters Kayaman et al 1999;Blanco et al 1996Blanco et al , 2003Karadag et al 1996). It was reported that hydrogels of acrylamide and itaconic acid exhibit very high capability to absorb water and have good biocompatibility (Blanco et al 1996;Karadag et al 1996).…”
mentioning
confidence: 99%
“…These results indicate that the equilibrium swelling ratio, q w , increases slightly with degradation of copolymer component of semi-IPNs. In simultaneous semi-IPN technique, it is found that crosslinking density decreases with the increase of linear polymer content, [32,41] implying that the presence of polyesteramide component restricts the crosslinking of PHEMA network. Hence, it can be concluded that M c of the semi-IPN is higher than pure PHEMA.…”
Section: Hydrolytic Degradationmentioning
confidence: 99%